First combined COMPASS/BeiDou-2 and GPS positioning results in Australia. Part I: single-receiver and relative code-only positioning - Odolinski, Robert; Teunissen, Peter; Odijk, Dennis (Taylor & Francis Asia Pacific (Singapore), 2014)
China's BeiDou-2/COMPASS is expected to deliver global Positioning, Navigation and Timing (PNT) services by 2020. Australia is already a beneficiary of the regional BeiDou configuration, as enough satellites are available to perform PNT. The present contribution is Part I out of two parts that consider first combined BeiDou+GPS positioning results in Australia. In Part II, we will focus our attention on the single-baseline RTK model performance and the integer ambiguity success rates. Part I considers code-only single- and multiple-frequency single-receiver and relative point positioning. Our results show that the increased strength of the combined model allows for improved positioning robustness and accuracy over the BeiDou- and GPS-only solutions.